Bessel Picosecond Laser Cutting Glass-Ceramics: Optimization of Processing Point Spacing, Incident Power, and Burst Mode - Xinjian Pan; Yunfei Duan; Yi Song; Cheng Peng; Jinxuan Li; Zhili Li; Chunjian Deng; Jianjun Yang; Qingguo Gao; Zhi Zhang; Yi Cai (Applied Sciences)
Recent advances in glass-ceramics research have expanded their applications in astronomy, optoelectronics, and laser systems. However, precision cutting technology remains challenging. This study optimized picosecond laser processing parameters for 600 nm-thick glass-ceramics, revealing critical influences of point spacing, laser energy, and pulse number. Atomic force microscopy showed that 1 µm processing spacing enabled uniform ablation grooves with optimal roughness. Two-pulse configurations achieved the most consistent surface improvement. At 12.5 W incident power, samples exhibited minimized average roughness (219 nm) with localized values reaching 208 nm, alongside 1.2 N breaking stress.